Stent-assisted coil embolization of challenging intracranial aneurysms: initial and mid-term results with low-profile ACCLINO devices - TÜRELİ, DERYA; BALTACIOĞLU, FEYYAZ (SPRINGER WIEN, 2016)
Stent-assisted coiling using low-profile, self-expandable and retrievable stents is a valid option in endovascular treatment of challenging intracranial aneurysms. This study aims to evaluate the feasibility and efficacy of ACCLINO 1.9 F and ACCLINO Flex stent systems, designed for use as adjunctive products in coil embolization of intracranial aneurysms. Case files of 47 patients, and 52 aneurysms in total, treated with at least one ACCLINO 1.9 F or ACCLINO Flex stent were retrospectively evaluated. Technical success, complications, and angiographic outcomes were assessed based on immediate post-procedural controls along with 6th and 12th month angiograms. Mechanical untoward event rate, including asymptomatic complications, is 9.6 % (five out of 52 aneurysms). Failed dual-stenting attempt rate is 15.4 % (two out of 13). Overall procedure-related morbidity is 4.2 % with no neurologic sequelae. Initial occlusion rate is 90.4 % (47 aneurysms). One patient had residual filling in the aneurysm neck, which was stable throughout follow-up. The remaining four cases had spontaneous follow-up occlusion. Recanalization rate at 6th month is 2.1 % with one aneurysm requiring retreatment. One patient was lost to follow-up. There is no mortality associated with treatment. Stent-assisted coil embolization with ACCLINO stents in single or dual configurations is a feasible treatment option for challenging intracranial aneurysms. Follow-up results are encouraging; techniques were effective in complex cases and there were no clinically significant adverse outcomes.
Keywords: Cerebral aneurysm; Stent-assisted coil embolization; Low-profile stent; LEO BABY STENTS; MANAGEMENT; NECK; OCCLUSION; SAFETY